Ambiente de aprendizaje y su incidencia en el rendimiento académico de los estudiantes de cuarto y quinto de la Unidad Educativa Adolfo María Astudillo, Babahoyo 2022 - Carpio Reyes, Alicia Rocio (2023)
Faced with a society that has evolved, education and academia need to be transformed to meet the expectations of a new and developed society, in which changes arise day by day and which because of this becomes more complex and, therefore, the teaching-learning process must also progress according to the demands of the general public. The learning environments must provide the students of the educational centers; the necessary conditions that allow problematizing, discovering, understanding, motivating and assimilating situations or educational content and daily life from their own perspectives. Learning environments must provide students with essential elements that promote teaching that stimulates the development of valuable skills and competencies throughout their lives, both personally and educationally. The objective of this case study is to know how the learning environment influences the academic performance of the fourth and fifth year students of the Adolfo María Astudillo Educational Unit in the city of Babahoyo for the 2022 academic period. questionnaire of questions addressed to all students in order to identify their current situation.